2018
DOI: 10.1103/physrevx.8.011002
|View full text |Cite
|
Sign up to set email alerts
|

Tunable-Range, Photon-Mediated Atomic Interactions in Multimode Cavity QED

Abstract: Optical cavity QED provides a platform with which to explore quantum many-body physics in drivendissipative systems. Single-mode cavities provide strong, infinite-range photon-mediated interactions among intracavity atoms. However, these global all-to-all couplings are limiting from the perspective of exploring quantum many-body physics beyond the mean-field approximation. The present work demonstrates that local couplings can be created using multimode cavity QED. This is established through measurements of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
241
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(252 citation statements)
references
References 63 publications
2
241
0
Order By: Relevance
“…The Dicke model is currently engineered in several experimental platforms [59][60][61][62][63][64]. We expect our results to be qualitatively insensitive to the details of the microscopic structure of the interaction termĤ int , and to hold in a broader set of models, and thus would be relevant for experiments where collectivity of the system is inevitably broken by inhomogeneous fields, or spatially varying light-matter couplings, or genuine inter-particle interactions such as using Rydberg atoms [65][66][67][68]. The stabilization of Dicke-TC order seen for strong ferromagnetic spin-spin interactions can also be generalized to systems where the inter-spin interactions have an anti-ferromagnetic character (J>0), given the capability to control atom-light coupling in cavity experiments [69].…”
Section: Discussionmentioning
confidence: 89%
“…The Dicke model is currently engineered in several experimental platforms [59][60][61][62][63][64]. We expect our results to be qualitatively insensitive to the details of the microscopic structure of the interaction termĤ int , and to hold in a broader set of models, and thus would be relevant for experiments where collectivity of the system is inevitably broken by inhomogeneous fields, or spatially varying light-matter couplings, or genuine inter-particle interactions such as using Rydberg atoms [65][66][67][68]. The stabilization of Dicke-TC order seen for strong ferromagnetic spin-spin interactions can also be generalized to systems where the inter-spin interactions have an anti-ferromagnetic character (J>0), given the capability to control atom-light coupling in cavity experiments [69].…”
Section: Discussionmentioning
confidence: 89%
“…[] showed that the onset of self‐organization can be mapped to the superradiant transition of the Dicke model, see Section 2. This study was later extended to narrow linewidth and multimode cavities.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…In the future, our multiplexed atom-cavity system may be combined with nonlinear cavity-mediated interactions or quantum nondemolition measurements that would enable universal quantum operations between spin waves. The demonstration here, of spin-wave multiplexed cavity electrodynamics, is a significant step toward these goals.Our apparatus is complementary to an active body of ensemble multiplexing research, using both spatial and spectral degrees of freedom [13][14][15][16][17][18][19][20][21][22][23]. Recently, a spatial array of single-photon detectors has been used to resolve 665 independent spin waves in an atomic ensemble [24,25].…”
mentioning
confidence: 99%